Community vulnerability to climate change in the context of other exposure-sensitivities in Kugluktuk, Nunavut - Prno, J; Bradshaw, B; Wandel, J; Pearce, T; Smit, B; Tozer, L (Polar Research, 2011)
Climate change in the Canadian north is, and will be, managed by communities that are already experiencing social, political, economic and other environmental changes. Hence, there is a need to understand vulnerability to climate change in the context of multiple exposure-sensitivities at the community level. This paper responds to this perceived knowledge need based on a case study of the community of Kugluktuk in Nunavut, Canada. An established approach for vulnerability assessment is used to identify current climatic and non-climatic exposure-sensitivities along with their associated contemporary adaptation strategies. This assessment of current vulnerability is used as a basis to consider Kugluktuk’s possible vulnerability to climatic change in the future. Current climate-related exposure-sensitivities in Kugluktuk relate primarily to subsistence harvesting and community infrastructure. Thinner and less stable ice conditions and unpredictable weather patterns are making travel and harvesting more dangerous, and some community infrastructure is sensitive to permafrost melt and extreme weather events (e.g., flash floods). The ability of individuals and households to adapt to these and other climatic exposure-sensitivities is influenced by non-climatic factors which condition adaptive capacity, including substance abuse, the erosion of traditional knowledge and youth suicide. These and other non-climatic factors often underpin adaptive capacity to deal with and adapt to changing conditions and must be considered in an assessment of vulnerability. This research argues that Northern communities are challenged by multiple exposure-sensitivities, beyond just those posed by climate, and effective adaptation to climate change requires consideration if not resolution of socio-economic and other issues in communities.